An Analysis of Students’ Recount Text by Using Systemic Functional Grammar - Iin Nurohmah (Universitas Pendidikan Indonesia (UPI), 2013)
The present study entitled An Analysis of Students’ Recount Text by Using Systemic Functional Grammar aims at investigating students’ writing Recount text by identifying schematic structure and linguistic features of the text. The data resources were six pieces of Recount text written by the eighth semester students of English Department who were treated as respondents. To analyze the texts, transitivity of functional grammar developed by Halliday (1994) was applied to identify the linguistic features of the texts. Meanwhile, the schematic structure of Recount is adopted from Anderson and Anderson (2003) which was used to analyze the schematic structure of the text. The findings show that most students seemed to be able to apply the schematic structure of Recount because they put the schematic structure correctly in different paragraphs. However there was still one student (the writer of text 6) who put the schematic structure in one paragraph only. Dealing with the linguistic features, most students likely found problems in differentiating between the use of simple present tense, past tense, prepositional phrases, regular and irregular verbs. Therefore, it is recommended for the students to improve their knowledge and practice more in writing, particularly in writing Recount.Keywords: functional grammar, linguistic features, schematic structure, recount text